Hybrid-Functional Calculations on the Incorporation of Na and K Impurities into the CuInSe2 and CuIn5Se8 Solar-Cell Materials - Ghorbani, Elaheh; Kiss, Janos; Mirhosseini, Hossein; Roma, Guido; Schmidt, Markus; Windeln, Johannes; Kiihne, Thomas D.; Felser, Claudia (Journal of Physical Chemistry C, 2015)
We have studied the energetics, atomic, and electronic structure of Na and K point defects, as well as the (Na-Na), (K-K), and (Na-K) dumbbells in CuInSe2 and CuIn5Se8 solar cell materials by hybrid functional calculations. We found that although Na and K behaves somewhat similar; there is a qualitative difference between the inclusion of Na and K impurities. Namely, Na will be mostly incorporated into CuInSe2 and CuIn5Se8 either as an interstitial defect coordinated by cations, or two Na impurities will form (Na-Na) dumbbells in the Cu sublattice. In contrast to Na, K impurities are less likely to form interstitial defects. Instead, it is more preferable to accommodate K either as KCu substitutional defect, or to form (K-K) dumbbells on Cu substitution positions. Our data show that all (Na-Na), (Na-K), and (K-K) dumbbells can form in both CuInSe2 and CuIn5Se8. In the Cu-poor CuIn5Se8 material the pristine Cu vacancies act as the most stable sites where Na and K can be inserted. The formation energy of Na-related defects is generally lower than the corresponding K-related defects, which would mean that if a defect site is already occupied by Na, then it is less likely that K is able to substitute Na during the postdeposition treatment. Regarding the electronic structure of the materials, Na and K point defects located in the Cu sublattice do not create deep defect levels in the gap, so they are not detrimental for the solar cell. In contrast, Se-related substitutional defects introduce defect levels in the gap, which act as charge traps, leading to severe degradation of the device efficiency. However, the formation energy of these Se-related defects are high so that they should have a low concentration in the material.
CRIS-Team Scopus Importer:2023-03-20